Circulating PEG-indoleamine 2,3-dioxygenase ameliorates diverse inflammatory diseases without toxicity or compromising immunocompetence - Jennifer A. Simonovich; Ryan A. Clark; Alexander J. Kwiatkowski; Madeline J. Fuchs; Mariana E. Viso; Chen Lu; Sabrina L. Macias; Isabella Pinto; Abhishek P. Shrestha; Tran B. Ngo; Sergio Duarte; Yong He; et al. (Proceedings of the National Academy of Sciences, 2026)
Indoleamine 2,3-dioxygenase (IDO), the enzyme responsible for tryptophan catabolism, is protective in many autoimmune and inflammatory diseases. We previously developed a localized immunomodulation approach through the fusion of IDO to a carbohydrate binding protein [E. Bracho-Sanchez et al. , Nat. Biomed. Eng. 7 , 1156–1169 (2023)]. Here we further develop IDO as a protein therapeutic for inflammation, investigating systemic delivery via conjugation of poly(ethylene glycol) (PEG) to IDO. PEGylation extended circulation time and treatment PEG-IDO demonstrated therapeutic efficacy in five autoimmune and inflammatory models. Treatment with a single dose of PEG-IDO resulted in reversal of hind limb paralysis in experimental autoimmune encephalomyelitis as model of multiple sclerosis; protected against hepatic damage in liver ischemia-reperfusion injury; prevention of abdominal aortic aneurysm; and decreased severity of imiquimod-induced psoriasis. Treatment with two doses of PEG-IDO provided maintenance of body weight and colon length in acute ulcerative colitis. PEG-IDO treatment increased regulatory T cell populations and reduced pathogenic Th17 cell populations and inflammatory cytokine production. Systemic delivery of PEG-IDO had little-to-no off-target effects. Mice maintained immunocompetency, clearing the Listeria monocytogenes infection, and had no observed toxicity. Additionally, PEG-IDO increased serum kynurenine, consistent with a kynurenine-mediated mechanism of action. These findings demonstrate systemic immunomodulation via circulating PEG-IDO ameliorates a breadth of disparate autoinflammatory diseases, protecting against inflammation-driven tissue destruction in spinal cord, liver, abdominal aorta, skin, and colon, while presenting a positive safety profile, and expanding the scope of potential applications for this therapeutic approach.